High-fat diet-induced adipose tissue-resident macrophages, T cells, and dendritic cells modulate chronic inflammation and adipogenesis during obesity - Mandal, Mousumi; Mamun, Md Abdullah Al; Rakib, Ahmed; Singh, Udai P. (Frontiers in Immunology, 2025)
BackgroundObesity is one of the major healthcare challenges and socio-economic liabilities worldwide and is rapidly reaching pandemic proportions. Characterized by low-grade chronic inflammation in adipose tissue (AT), the development of obesity is influenced by genetic, neurologic, and metabolic factors, immune activation, and behavioral activities. During obesity, AT macrophages play a central role in inflammation, lipid metabolism, and mitochondrial function in adipocytes. In this study, we investigated how AT resident macrophages, T cells, and dendritic cells (DCs) communicate to coordinate and regulate AT inflammation during obesity.MethodsWe performed contact mode ex-vivo co-culture of different combinations of AT resident immune cells from mice fed with high-fat diet (HFD) and normal diet (ND) and also 3T3-L1 adipocytes with macrophages, T cells, and DCs isolated from AT of mice fed HFD. We analyzed the expression of adiposity-associated genes, inflammatory markers, and levels of cytokines and chemokine in conditioned culture medium. We also analyzed adipogenesis and performed Oil Red O staining of co-cultured adipocytes to visualize lipid accumulation under these conditions.ResultsWe found that macrophages from AT derived from HFD-fed mice fueled adipogenesis and inflammation in 3T3-L1 adipocytes and stromal vascular fraction cells derived from ND AT. Macrophages from HFD AT also promoted the expression in ND-derived T cells of chemokines including CCL5 and CXCL10 and inflammatory cytokines including TNF-α, IL-1β, IFN-γ, and IL-17A. Interestingly, T cells from HFD AT also induced expression of inflammatory genes in ND macrophages and lipid accumulation and expression of inflammatory proteins like CXCL2, CCL3, and CCL4 in 3T3-L1 adipocytes. DCs also stimulated adipocyte differentiation, and expression of chemokines and inflammatory cytokines like CCL5, MCP-3, and TNF-α in 3T3-L1 adipocytes.ConclusionsOur findings suggest that during obesity, macrophages work together in a coordinated fashion to modulate the activities of T cells, stimulating adipocyte differentiation, and thereby sustaining chronic inflammation. Thus, macrophages in AT might serve as druggable targets in combatting obesity.